Dynamics of the entrepreneurial process: The role of bricolage and effectuation - Scazziota, V. V.; Guerrazzi, L.; Serra, F. A. R. (80th Annual Meeting of the Academy of Management, 2020)
Effectuation and bricolage are two of the alternative theoretical approaches to entrepreneurship that provide explanations about the entrepreneurial activity in dynamic and resource-limited environments. The focus of this study will be on effectuation and bricolage, considering the need to broaden our understanding of entrepreneurial action beyond the traditional analysis of effectuation and causation. We used a longitudinal process approach to answer the following research questions: How does the entrepreneurial process occur in the light of the effectuation and bricolage? Why does it happen? We analyzed 120 events that influenced the entrepreneurial process in 4 ventures. Our results improved our understanding of the dynamics between bricolage, effectuation, and causation as modes of actions. We showed that bricolage is a preferred mode of action to capture resources and knowledge about these resources to extend its services, while effectuation is a preferred mode of action to acquire abilities. Causation seems to occur due to internal factors, such as the need to internalize routines and structures to improve the business process to gain efficiency or by the pressure of external stakeholders."